Norcantharidin inhibits TOP2A expression via H3K27me3 mediated epigenetic regulation to alleviate the progression of hepatocellular carcinoma - Ruibing Wu; Hengye Yuan; Yuehua Wang; Xianggang Gou; Wanhua Hou; Zhongzheng Zhou; Xinran Wang; Xiuling Deng; Changshan Wang; Haisheng Wang; Jia Yan; Jia Yan (Frontiers in Pharmacology)
BackgroundNorcantharidin (NCTD), a bioactive compound derived from traditional Chinese medicine, has demonstrated promising anticancer activity against multiple malignancies, particularly hepatocellular carcinoma (HCC). However, its epigenetic regulatory mechanisms and associated transcriptional consequences remain poorly characterized.MethodsIn this study, we integrated biochemical assays with a panel of cellular analyses assessing cell viability, proliferation, colony formation, and migratory capacity to investigate NCTD’s therapeutic potential in HCC progression. Potential molecular targets of NCTD were systematically identified through integrated network pharmacology approaches. Chromatin immunoprecipitation quantitative PCR (ChIP-qPCR) was performed to quantify H3K27me3 enrichment level at the TOP2A locus in NCTD-treated HCC cells. Molecular docking simulations were employed to examine structural interactions between NCTD and EZH2 (enhancer of zeste homolog 2), while co-immunoprecipitation assays were further conducted to validate protein-protein interactions between EZH2 and protein phosphatase 1 (PP1).ResultsWe identified topoisomerase IIα (TOP2A) as a critical molecular target mediating NCTD’s anti-HCC effects. Functional characterization revealed that NCTD significantly attenuated HCC cell proliferation and induced G2/M phase cell cycle arrest through disruption of the TOP2A-p53 signaling axis. Mechanistic investigations demonstrated that NCTD epigenetically suppresses TOP2A transcription via PRC2 (Polycomb Repressive Complex 2)-mediated deposition of the repressive histone mark H3K27me3 at the TOP2A promoter. Structural biology analyses confirmed direct binding of NCTD to EZH2 protein, consequently impairing PP1-mediated dephosphorylation and enhancing PRC2 complex stability.ConclusionOur findings establish that NCTD exerts anticancer effects in HCC through epigenetic silencing of TOP2A. This work not only elucidates a novel pharmacoepigenetic mechanism underlying NCTD’s antitumor activity but also provides translational rationale for developing PRC2-targeted therapeutic strategies in HCC management.